P-134 Subcutaneous lidocaine infusion for complex pain in hospice inpatients – a preliminary report. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Lee, Jasmine; Hall, Emma; George, Rob
Abstract : Background: Neuropathic pain is common and challenging to treat. Systemic lidocaine, a local anaesthetic, has established use in pain management (Eipe, Gupta & Penning, 2016). Intermittent lidocaine infusions are safe, better than placebo and equally effective as other analgesics such as morphine (Challapalli, Tremont-Lukats, McNicol, Lau et al ., 2005). Anecdotes of subcutaneous lidocaine infusions also report effectiveness in some cancer patients (Seah, Herschtal, Tran, Thakerar et al ., 2017). To our knowledge use in palliative care patients has not been reported. Aims: To describe and evaluate subcutaneous lidocaine infusions in hospice inpatients; To assess from patients' and clinicians' observations if lidocaine is feasible, potentially effective, safe and tolerable. Method: Sequential retrospective review of hospice inpatients over seven months (November 2018 to May 2019) given subcutaneous lidocaine infusion for refractory pain. Patients were given a 2% lidocaine dose per 24 hours by CSCI. IPOS scores and documentary text were analysed at day 0, 1 and 3. Results: Twelve patients (eleven with malignancy) received lidocaine. All had complex pain, strong opioids and co-analgesia. Eight required anaesthetic intervention. In seven pain scores improved. Drowsiness improved in seven. Two with worsening pain were close to death however, benefited in alertness. Overall two showed no improvement in either pain or drowsiness. All tolerated lidocaine well for periods up to 122 days (median 7). One stopped prematurely due to incidental sepsis. One experienced opioid toxicity after dose increase which may be ascribed to lidocaine effects. One continued lidocaine at home and for >4 months. Conclusions: In this preliminary report, for patients with complex pain, refractory to standard multidrug regimes, lidocaine is a well-tolerated, safe, potential option for hospice inpatient use and supports the available anecdotal evidence. Observations suggest benefits in pain control and quality of life. Lidocaine appears particularly valuable where patients are experiencing drowsiness from high frequency or high dose opioids; as an option pending anaesthetic intervention and; inpatients unable to swallow conventional neuropathics. These findings justify a formal study which is under development.